Digital Government Innovation in Election Monitoring: An Evaluation of the Implementation of Siwaslu in the 2024 Election - Nur Hidayat; Alberto Noviano Patty; M Mujiburrahman (Universitas Muhammadiyah Tangerang, 2026)
This Research aims to analyze digital government innovations in election monitoring through an evaluation of the implementation of the Election Monitoring Information System (Siwaslu) in the 2024 Elections. The approach used is qualitative-exploratory, focusing on the analysis of the system's functionality, the effectiveness of its utilization by monitoring actors, and the identification of the strengths and limitations of the implementation. Data were collected through institutional documentation, Siwaslu utilization reports, in-depth interviews, and focus group discussions (FGDs), which were then analyzed thematically using a data-driven analysis approach. This study employs the frameworks of Digital Governance, Public Sector Innovation, and State Capacity to evaluate Siwaslu's contribution to the transformation of election oversight governance. The findings indicate that Siwaslu has successfully enhanced efficiency, data accuracy, and real-time oversight capacity through the digitization of reporting and documentation processes. This system also strengthens vertical integration within the oversight structure and provides a database that supports evidence-based policy-making and legal substantiation in election disputes. However, the implementation of Siwaslu still faces a number of challenges, particularly regarding limited access to digital infrastructure in less-developed regions, low digital literacy among users, and sub-optimal integration with other systems within the Bawaslu oversight ecosystem. Result of research indicate the existence of an innovation gap a disparity between innovation potential and implementation, that encompasses aspects of access, capacity, and system integration. Thus, this study concludes that Siwaslu is a significant digital government innovation in strengthening election oversight in Indonesia, yet it remains in a transitional phase toward a more mature and integrated system. Strengthening digital infrastructure, enhancing human resource capacity, and developing system interoperability are key factors in optimizing Siwaslu''s role as an instrument of transparent, accountable, and data-driven election governance. Penelitian ini mengevaluasi implementasi Sistem Informasi Pengawasan Pemilu (Siwaslu) dalam Pemilu 2024 di Indonesia dengan menggunakan kerangka kerja analitis terintegrasi yang menggabungkan Tata Kelola Digital, Inovasi Sektor Publik, dan Kapasitas Negara. Dengan menggunakan pendekatan studi kasus kualitatif dan desain evaluasi interpretatif, data dikumpulkan melalui dokumen kelembagaan, wawancara mendalam, dan diskusi kelompok terfokus, kemudian dianalisis menggunakan analisis tematik. Temuan menunjukkan bahwa Siwaslu telah secara signifikan meningkatkan efisiensi, akurasi data, dan kapasitas pemantauan real-time, yang mencerminkan perannya sebagai inovasi adaptif-inkremental di sektor publik. Namun, studi ini mengidentifikasi “celah inovasi” antara desain sistem dan implementasinya, yang terwujud dalam tiga dimensi: (1) celah akses akibat infrastruktur digital yang tidak merata, (2) celah kapasitas terkait tingkat literasi digital yang bervariasi di antara pengguna, dan (3) celah integrasi yang disebabkan oleh keterbatasan interoperabilitas antar sistem. Mengartikan, meskipun Siwaslu berkontribusi dalam memperkuat kapasitas negara dalam pengawasan pemilu, efektivitasnya bergantung pada kesiapan ekosistem pendukung. Studi ini memberikan kontribusi pada literatur dengan memberikan evaluasi empiris terhadap sistem pengawasan digital di negara-negara demokrasi yang sedang berkembang dan menyoroti pentingnya mengintegrasikan inovasi teknologi dengan pengembangan kapasitas kelembagaan dan sumber daya manusia.